Automatic Summarization of Court Decision Documents over Narcotic Cases Using BERT - Wicaksono, Galih Wasis; Al asqalani, Sheila Fitria; Azhar, Yufis; Hidayah, Nur Putri; Andreawana, Andreawana (Society of Visual Informatics, 2023)
Reviewing court decision documents for references in handling similar cases can be time-consuming. From this perspective, we need a system that can allow the summarization of court decision documents to enable adequate information extraction. This study used 50 court decision documents taken from the official website of the Supreme Court of the Republic of Indonesia, with the cases raised being Narcotics and Psychotropics. The court decision document dataset was divided into two types, court decision documents with the identity of the defendant and court decision documents without the defendant's identity. We used BERT specific to the IndoBERT model to summarize the court decision documents. This study uses four types of IndoBert models: IndoBERT-Base-Phase 1, IndoBERT-Lite-Bas-Phase 1, IndoBERT-Large-Phase 1, and IndoBERT-Lite-Large-Phase 1. This study also uses three types of ratios and ROUGE-N in summarizing court decision documents consisting of ratios of 20%, 30%, and 40% ratios, as well as ROUGE1, ROUGE2, and ROUGE3. The results have found that IndoBERT pre-trained model had a better performance in summarizing court decision documents with or without the defendant's identity with a 40% summarizing ratio. The highest ROUGE score produced by IndoBERT was found in the INDOBERT-LITE-BASE PHASE 1 model with a ROUGE value of 1.00 for documents with the defendant's identity and 0.970 for documents without the defendant's identity at a ratio of 40% in R-1. For future research, it is expected to be able to use other types of Bert models such as IndoBERT Phase-2, LegalBert, etc.